Pengaruh Teknologi Informasi terhadap Proses Pembelajaran dan Prestasi Akademik Mahasiswa - Hasan, Nor; Soewarno, Noorlailie; Isnalita, Isnalita (Universitas Swadaya Gunung Jati, 2019)
This study aimed to obtain empirical evidence regarding the correlation of the use of information technology to the learning process (lectures) and its impact on student academic achievement. This study used path analysis or analysis that not only tested the direct influence of independent variable to the dependent variable, but also explained the presence or absence of indirect influence given by the independent variable through the intervening variable to the dependent variable. This study uses questionnaires media that are disseminated through electronic media. The statements contained in the questionnaire were measured using the Likert scale of 5 (five) points, then processed using Path Analysis, and interpreted. Total respondents in this study as many as 204 students of Master of Accounting who have been through the course of information technology management. The results of this study indicate that information technology influences student academic achievement and influences the learning process and has an impact on student academic achievement.Keywords : Information technology; Learning process; Student academic achievement.